The Effect of Ethyl Alcohol on the Function of Spatial Memory in Rats - Ratajczak, P.; Kus, K.; Jarmuszkiewicz, Z.; Woźniak, A.; Nowakowska, E. (Arzneimittelforschung, 2012)
Alcoholism is a mental disease in the course of which depression, anxiety, and cognitive function deficits may appear, and these symptoms can be aggravated by comorbid schizophrenia.The aim of this study was to find whether spatial memory (Morris Water Maze) function impairment is found in prenatally stressed rats (PSG) (prenatal stress paradigm – animal model of schizophrenia) and whether aripiprazole ARI and olanzapine OLA modify these functions. It was also important to study the effect of ethyl alcohol administered to rats.Behavioural tests showed that ARI and OLA improved spatial memory in the non-stressed control group (NSCG) and in the PSG. Moreover, spatial memory in the non-stressed alcohol group (NSAG) improved significantly compared to the NSCG, while in the prenatally stressed alcohol group (PSAG) spatial memory improved both in comparison to the NSCG and PSG. No statistically significant differences were found by comparing groups which received ethyl alcohol (NSAG, PSAG).
Keywords: aripiprazole; olanzapine; prenatal stress; spatial memory; ethanol; rats